RI 7927 Removal of Lead and Zinc and the Production of Prereduced Pellets From Iron and Steelmaking Wastes - W. M. Dressel (The National Institute for Occupational Safety and Health (NIOSH), 1974)
Over 2 million tons of steel furnace dust containing approximately 100,000 tons of zinc and 10,000 tons of lead are produced each year. Recycling of the dusts would conserve mineral resources, lessen land area requirements for disposal, decrease pollution problems, and aid in solving our balance of payment problem. Steelmaking dusts can be pelletized and thermally treated to remove lead and zinc and to reduce the iron oxide to form metallized pellets. In laboratory tests more than 99 pct of the zinc and 85 pct of the lead was volatilized from the dust by roasting at 1,000° C in carbon monoxide. The volatilized material can be collected and treated further for lead and zinc recovery. Reduction and volatilization of over 95 pct of the zinc and most of the lead was achieved by roasting self-reducing mixtures of steel furnace dusts and high carbon steelmaking wastes in an inert atmosphere at 1,100° C. Over 80 pct of the iron in the resulting pellets was metallized.